2011
DOI: 10.1534/genetics.111.128256
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Survival in a Clinical Saccharomyces cerevisiae Isolate Is Influenced by a Major Quantitative Trait Nucleotide

Abstract: One of the major challenges in characterizing eukaryotic genetic diversity is the mapping of phenotypes that are the cumulative effect of multiple alleles. We have investigated tolerance of oxidative stress in the yeast Saccharomyces cerevisiae, a trait showing phenotypic variation in the population. Initial crosses identified that this is a quantitative trait. Microorganisms experience oxidative stress in many environments, including during infection of higher eukaryotes. Natural variation in oxidative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…cerevisiae isolates have been responsible for human infections that are not life threatening except in severely immunocompromised patients where systemic infection may occur 22 . Pathogenic Saccharomyces clinical strains have shown resistance to high oxidative stress conditions 44 . Upon exposing the S .…”
Section: Discussionmentioning
confidence: 99%
“…cerevisiae isolates have been responsible for human infections that are not life threatening except in severely immunocompromised patients where systemic infection may occur 22 . Pathogenic Saccharomyces clinical strains have shown resistance to high oxidative stress conditions 44 . Upon exposing the S .…”
Section: Discussionmentioning
confidence: 99%
“…S. cerevisiae displays many quantitative traits that are also important in other cell types, including industrial microorganisms and cells of higher, multicellular organisms. Such properties include thermotolerance [6] and oxidative stress tolerance [7], the capacity to produce small molecules, such as acetic acid [8] and ethanol tolerance [9], [10]. Other quantitative traits that have been studied in yeast include transcriptional regulation [11], sporulation efficiency [12], telomere length [13], cell morphology traits [14], mitochondrial genome instability [15], global gene expression [16], evolution of biochemical pathways [17] and resistance to chemicals [18].…”
Section: Introductionmentioning
confidence: 99%
“…In S. cerevisiae , the main role of proper oxidative stress response virulence has been suggested since a virulent strain mutant in transcription factor Yap1p, the main transcription factor involved in oxidative stress response that is unable to grow under oxidative stress conditions, presented low survival levels in human blood compared with the wild type or the YAP1 reconstituted strain ( Llopis et al, 2012 ). Diezmann and Dietrich (2011) compared hundreds of clinical isolates and showed that they were more resistant to oxidative stress after they verified the central role of oxidative stress resistance in S. cerevisiae virulence.…”
Section: S Cerevisiae Infection Mechanismsmentioning
confidence: 99%